1998
DOI: 10.1023/a:1018860909826
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A method is proposed to allow a more accurate evaluation of thermogravimetric data to identify diffusion or partial diffusion control of scaling kinetics. This method is based on the ® tting of mass-gain data to a parabola over a short time interval. The translation of the time interval over the entire test time period provides an actual instantaneous parabolic rate constant independently of any transient stage or simultaneous reaction steps. The usefulness and limitations of this procedure are illustrated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(92 citation statements)
references
References 12 publications
5
86
0
1
Order By: Relevance
“…Given that the grain size was the only microstructural variable that differed among the three, changes in oxidation rate can be attributed to a grain size effect. An increase in the total grain boundary length at the surface corresponds to an increase in the available high diffusivity paths for ion transport; this microstructural effect on oxidation rate has been suggested previously [5,6,9,16,[26][27][28]. The effect of grain size (or total grain boundary length) on oxidation rate may also be evident in the studies of orientation effects in polycrystals.…”
Section: Grain Size Dependence Of Oxidationsupporting
confidence: 52%
“…Given that the grain size was the only microstructural variable that differed among the three, changes in oxidation rate can be attributed to a grain size effect. An increase in the total grain boundary length at the surface corresponds to an increase in the available high diffusivity paths for ion transport; this microstructural effect on oxidation rate has been suggested previously [5,6,9,16,[26][27][28]. The effect of grain size (or total grain boundary length) on oxidation rate may also be evident in the studies of orientation effects in polycrystals.…”
Section: Grain Size Dependence Of Oxidationsupporting
confidence: 52%
“…1) has been applied to the experimental data, the mass gain is normalized by the surface area of the powder (Fig. 8) [7]. The fitted value of k p is equal to 2.5 9 10 -12 g 2 cm -4 s -1 in agreement with the literature data for Cr 2 O 3 growth (at 800°C: k p = 8 9 10…”
Section: Discussionsupporting
confidence: 79%
“…This morphology was observed between 800 °C and 950 °C, and generally contains high concentration of vacancies, which can lead to cavities nucleation [32] . The EDS analysis carried out on the external surface on this intermetallic indicated that mainly is Al 2 O 3 , whereas the iron detected indicates that the formation of an iron oxide would be possible.…”
Section: Figura 6 A) Meb De Los Productos De Corrosión Formados Sobrmentioning
confidence: 99%